In the shadows of snow leopards and the Himalayas: density and habitat selection of blue sheep in Manang, Nepal. Issue 1 (23rd November 2020) - Filla, Marc; Lama, Rinzin Phunjok; Ghale, Tashi Rapte; Signer, Johannes; Filla, Tim; Aryal, Raja Ram; Heurich, Marco; Waltert, Matthias; Balkenhol, Niko; Khorozyan, Igor
Abstract: There is a growing agreement that conservation needs to be proactive and pay increased attention to common species and to the threats they face. The blue sheep ( Pseudois nayaur ) plays a key ecological role in sensitive high‐altitude ecosystems of Central Asia and is among the main prey species for the globally vulnerable snow leopard ( Panthera uncia ). As the blue sheep has been increasingly exposed to human pressures, it is vital to estimate its population dynamics, protect the key populations, identify important habitats, and secure a balance between conservation and local livelihoods. We conducted a study in Manang, Annapurna Conservation Area (Nepal), to survey blue sheep on 60 transects in spring (127.9 km) and 61 transects in autumn (134.7 km) of 2019, estimate their minimum densities from total counts, compare these densities with previous estimates, and assess blue sheep habitat selection by the application of generalized additive models (GAMs). Total counts yielded minimum density estimates of 6.0–7.7 and 6.9–7.8 individuals/km 2 in spring and autumn, respectively, which are relatively high compared to other areas. Elevation and, to a lesser extent, land cover indicated by the normalized difference vegetation index (NDVI) strongly affected habitat selection by blue sheep, whereas the effects of anthropogenic variables were insignificant. Animals were found mainly in habitats associated with grasslands and shrublands at elevations between 4, 200 and 4, 700 m. We show that the blue sheep population size in Manang has been largely maintained over the past three decades, indicating the success of the integrated conservation and development efforts in this area. Considering a strong dependence of snow leopards on blue sheep, these findings give hope for the long‐term conservation of this big cat in Manang. We suggest that long‐term population monitoring and a better understanding of blue sheep–livestock interactions are crucial to maintain healthy populations of blue sheep and, as a consequence, of snow leopards. Abstract : Blue sheep play a key ecological role in high‐altitude ecosystems and represent the staple prey for the globally threatened snow leopard. We show that the Manang area, Annapurna Conservation Area, Nepal, still maintains a relatively high density of these ungulates. Elevation and land cover are the main local determinants of blue sheep habitats.